1989
DOI: 10.3758/bf03208056
|View full text |Cite
|
Sign up to set email alerts
|

Examination of apparent extent as an explanation of the Poggendorff effect

Abstract: The explanation of apparent misalignment in the Poggendorff figure, based on underestimation of the intertransversal distance, was investigated in two experiments. In Experiment 1, subjectsjudged the intertransversal distance in the traditional Poggendorfffigure and two of its variants. The size of the acute angle and the intertransversal distance were manipulated. Half of the subjects made the judgments with the method used by Wilson and Pressey (1976) and the other half made their judgments with the method u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…*Converted to intertransversal extent (see Weintraub & Krantz , 1971 Despite this research on the relationship between the Poggendorff and Miiller-Lyer illusions and controversy regarding a common causal basis in these illusions (e.g. , Day , Jolly , & Duffy, 1987;Trueman & Wilson , 1989), it must be stressed here that we have consistently encountered differences in the variability of the two illusory effects. In the correlational study noted above, the variability in the responses to the wings-in and wings-out MullerLyer figures was substantially greater than the variability observed for Poggendorff alignment judgments (see Table 1).…”
mentioning
confidence: 91%
“…*Converted to intertransversal extent (see Weintraub & Krantz , 1971 Despite this research on the relationship between the Poggendorff and Miiller-Lyer illusions and controversy regarding a common causal basis in these illusions (e.g. , Day , Jolly , & Duffy, 1987;Trueman & Wilson , 1989), it must be stressed here that we have consistently encountered differences in the variability of the two illusory effects. In the correlational study noted above, the variability in the responses to the wings-in and wings-out MullerLyer figures was substantially greater than the variability observed for Poggendorff alignment judgments (see Table 1).…”
mentioning
confidence: 91%
“…Greist-Bousquet and associates (e.g., Greist-Bousquet & Schiffman, 1981, 1985Greist-Bousquet, Schiffman, Dorsett, & Davis, 1989a) have been actively promoting a distance-misperception hypothesis grounded on the Milller-Lyer (arrowhead) display, arguing that misperception of the distance between the arrowheads is applicable to the Poggendorff display. They have been challenged by Trueman and Wilson (1989) and Day, Jolly, and Duffy (1987). Some years ago, my decision was to reject a parallels-attract version of the distance-misperception hypothesis .…”
Section: For the Poggendorffdisplay (Transversal Interrupted By Paralmentioning
confidence: 99%
“…(The two physical distances, each with an associated perceived distance must be distinguished; cf. Trueman & Wilson, 1989). Greist-Bousquet and Schiffman (1981), Trueman and Wilson (1989), and Weintraub and Tong (1974) have employed a dot-setting task that permits the observer to set the distance and orientation between a pair of free-standing dots to match perceptually the intertransversal slant distance and direction in a Poggendorff display.…”
Section: Perceptual Plane Geometry: the General Casementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Finlay and Caelli (1975) and Wilson and Pressey (1976) reported overestimation of interparallel extent. Recently, Trueman and Wilson (1989) found that apparent alignment judgments and judgments of intertransversal distance did not follow similar trends, and others (Day, Jolly, & Duffy, 1987;Wenderoth & O'Connor, 1987) In this experiment, the magnitude of the Poggendorff illusion was monitored at I-min intervals over a 5-min period. The primary issue investigated here was whether or not inspection of the obtuse-and the acute-angle Poggendorff variants differentially affected the magnitude of the Poggendorff illusion over the 5-min inspection period, as might be expected from Greist-Bousquet and Schiffman's apparent distance theory.…”
mentioning
confidence: 99%